Charles Dickens and his performing selves : Dickens and the public readings - Andrews, Malcolm, 1942- (OUP E-Books., 2006)
Charles Dickens's public readings have not had the attention they deserve; and yet Dickens put as much effort into perfecting his performances as he did with his novels. These performances were sensational events and won Dickens thousands of new admirers. This book tells that story and brings the events alive, with more detail than ever before. - ;Charles Dickens had three professional careers: novelist, journalist and public Reader. That third career has seldom been given the serious attention it deserved. For the last 12 years of his life he toured Britain and America giving 2-hour readings.